A closure study of ocean inherent optical properties using flow cytometry measurements. (January 2020) - Zhao, Yangyang; Poulin, Carina; McKee, David; Hu, Lianbo; Agagliate, Jacopo; Yang, Ping; Xiaodong, Zhang
Highlights: Detailed particle characteristics were studied for optical closure. Use of a single slope and one refractive index underestimates particle complexity. Lorenz-Mie and more complex particle shape and structure models performed broadly. Backscattering is sensitive to detailed size and refractive index distribution. Particles between 0.5–20 µm contribute significantly to the IOPs. Abstract: Flow cytometry and inherent optical property measurements of UK coastal waters were used to evaluate optical closure of different combinations of models for particle size, refractive index and shape. The particle size and refractive index distributions were derived from flow cytometry measurements and subsequently simplified through averaging down to the simplest model consisting of a Junge size distribution with a single bulk refractive index. Models for particle shapes included homogeneous spheres, coated spheres, and hexahedra. The simplest particle model, based on a Junge size distribution and a single bulk refractive index, gave the poorest quality of closure, suggesting that it underestimates particle complexity in the sampled waters. Other particle models using more detailed combinations of size and refractive index distributions gave broadly equivalent results for absorption and scattering. Backscattering was better represented by the most complex particle size and refractive index model, indicating that backscattering is sensitive to those factors. The homogeneous spherical model gave relatively good results, which is expected because the inversion of size and refractive index distributions from flow cytometry is based on the homogeneous spherical model using forward and side scattering signals. Lorenz-Mie theory, assuming homogeneous spheres, provided optical closure that was generally as accurate as models with more complex particle shape and structure. Cumulative contribution simulations revealed that particles between 0.5 and 20 µm substantially contributed to attenuation, scattering and backscattering, while particles larger than 20 µm mainly contributed to absorption and small particles (< 0.5 µm) contribute to 30–40% of backscattering.